The Longwood guide to writing - Lunsford, Ronald F; Bridges, Charles W. (Allyn and Bacon, 2000)
Reflecting Ron Lunsford and Bill Bridges' fifty years of combined teaching experience and their commitment to (and understanding of) the writing process, The Longwood Guide to Writing is among the most engaging, up-to-date, and authoritative aims-based rhetorics on the market. In this text, the authors help students see the organic nature of the writing process by continually offering students the opportunity to examine and refine their own individual writing processes, rather than limiting them to a single one-size-fits-all process. Students are introduced to the various phases of the writing process, beginning with a wide variety of invention strategies, then they are invited to apply their creativity and what they have learned to a variety of writing "occasions" - from the personal essay to the persuasive to the literary. They learn effective ways to do research, write with sources, take essay exams, and create portfolios, and - in two unique chapters devoted to style - they learn how form affects content.